High lichen species richness in Polylepis australis forest: New records from South America and Argentina - Rodriguez, Juan Manuel (2020)
The Polylepis australis forests in Central Argentina support a great biodiversity in a relative small area. As a result of this study focusing on the diversity and ecology of the lichen communities of these forests, we present five new species for South America: Rinodina ficta, R. malcolmii, R. obscura, Usnea glabrata, Tetramelas triphragmioides and eight taxa new for Argentina: Calicium abietinum, Erioderma leylandii subsp. leylandii, Leptogium microstictum, Phaeophyscia endococcinodes, Rinodina dolichospora, R. intermedia, Usnea cirrosa and U. flavocardia. Unidentified Usnea species, similar to U. silesiaca, were also characterized and discussed.